Robotic mechanical wounding is sufficient to induce phenylacetaldoxime accumulation in Tococa quadrialata - Kilian Lucas Ossetek; Andrea Teresa Müller; Axel Mithöfer (Plant Signaling & Behavior)
This study investigated the accumulation of phenlyacetaldoxime (PAOx) and PAOx-Glc in Tococa quadrialata leaves in response to herbivore infestation and mechanical wounding. Results show that PAOx levels peaked at 24 h post-infestation, while PAOx-Glc remained present for several days. The accumulation of PAOx began as early as 3 h after herbivory, with PAOx-Glc significantly increased after 6 h. Mechanical wounding induced similar responses in PAOx and PAOx-Glc accumulation as herbivory, suggesting that continuous tissue damage triggers the production of these compounds. Interestingly, SpitWorm-treated leaves showed the highest levels of both PAOx and PAOx-Glc, indicating that herbivore-derived oral secretions (OS) play a role in the induction of these compounds. Additionally, JA-independent PAOx production was found to be associated with tissue damage rather than specific known signaling compounds. Emission of benzyl cyanide and 2-phenylethanol, PAOx-derived plant volatiles, was observed in response to herbivory and SpitWorm treatment providing plant-derived OS, further highlighting the role of herbivore cues in plant defense responses.